Encrusted cystitis after definitive radiotherapy for cervical cancer: a case report - Perrucci, Elisabetta; Lancellotta, Valentina; Benedetto, Maika di; Palumbo, Isabella; Matrone, Fabio; Chiodi, Marino; Lombi, Riccardo; Marcantonini, Marta; Mariucci, Cristina; Aristei, Cynthia (Journal of Contemporary Brachytherapy, 2016)
Purpose : Encrusted cystitis is a rare chronic inflammatory disease characterized by calcified plaques of the bladder, previously altered by varies conditions as urological procedures, caused by urea-splitting bacteria. Only one case has been reported on encrusted cystitis occurring after surgery and radiation therapy for a pelvic neoplasm. We report on encrusted cystitis occurred after definitive radiotherapy for bulky uterine cervix cancer, and examine the doses to the bladder wall and the procedure of radiation treatment performed as a possible cause of the onset of the disease. Case presentation : A 52-year-old female developed encrusted cystitis, caused by Corynebacterium spp., after 14 months from definitive chemo-radiotherapy and 2/D brachytherapy treatment for FIGO stage IB2 uterine cervix cancer. For pelvic radiotherapy, the mean bladder dose was 48.47 Gy (range 31.20–51.91); maximal bladder point doses at each brachytherapy insertions were 7.62 Gy, 4.94 Gy and 6.27 Gy at first, second, and third fraction, respectively. Total biological effective dose (BED) at bladder point was 140.05 Gy3. The patient was administered antibiotic therapy with linezolid and urine acidification with vitamin C; dietary norms were also suggested. After therapy, complete remission of symptoms and radiological findings were achieved, and the planned surgery for removing the calcified plaques was not completed. After 5 years from the cervical cancer diagnosis, the patient was disease-free without urinary symptoms. Conclusions : The high doses administered to the bladder wall and the repeated catheterizations performed at each brachytherapy insertions may have favored the infection and promoted the occurrence of the encrusted cystitis.